VCF file - Underwood, Zachary E.; Mandeville, Elizabeth G.; Walters, Annika W. (Dryad Digital Repository, 2015)
This is a .vcf file produced by calling variant genetic sites using samtools and bcftools. For each variant site identified, we required that >60% of all individuals had 1 or more read at that locus.